الكشف عن مستوى الصحة لنفسية لدى المرشدين التربويين العاملين في المدارس الثانوية: دراسة وصفية - خلف، حسين حسين زيدان; العزاوى، محمد عباس عبود; البشير، الصافى عيسى أحمد (جامعة النيلين - كلية الدراسات العليا, 2019)
The aim of this study is to measure the mental health level of educational counselors and to find statistical differences by gender variable to guide and guide the level of mental health. The researcher adopted the Shaalan scale (2017) consisting of (31) paragraphs divided into six areas. The scale was presented to a number of arbitrators (90%). The researcher applied the scale to the sample of the research, which represents the educational evidence in the city of Baquba (50). The researcher adopted the statistical analysis of the size and characteristics of reliability and stable stability, because the measure was recently built‘ and the researcher SPSS to analyze the data and extract the statistical indicators ‘ the results showed by comparing the arithmetic mean of the low level of mental health counselors with educational level, when compared with the explanatory and guidance Differences of statistical significance for the benefit of the workers compared to the guides, and in light of the results of the researcher put a number of recommendations and suggestions.
تهدف الدراسة الحالية إلى قياس مستوي الصحة النفسية لدي المرشدين التربوين، وإيجاد الفروق الإحصائية وفق متغير النوع للمرشدين والمرشدات لمستوي الصحة النفسية، تبني الباحثون مقياس (شعلان، 2017) والمكون من (31) فقرة مقسمة علي ستة مجالات، وقد عرض المقياس علي عدد من المحكمين وحاز علي موافقة (90%)، طبق الباحثون المقياس علي عينة الدراسة التي تمثل المرشدين التربويين في مدينة بعقوبة والبالغ عددهم (50) مرشد ومرشدة، وقد اعتمد الباحثون التحليل الإحصائي لمعد المقياس وكذلك الخصائص السايكومترية من صدق وثبات، لان المقياس تم بنائه حديثا، استخدم الباحثون الحقيبة الإحصائية (SPSS) لتحليل البيانات واستخراج المؤشرات الإحصائية، أظهرت نتائج الدراسة من خلال مقارنة المتوسط الحسابي والفرضي انخفاض مستوي الصحة النفسية للمرشدين التربويين، وعند مقارنة الأوساط الحسابية للمرشدين والمرشدات أظهرت فروق ذات دلالة إحصائية ولصالح المرشدين مقارنة بالمرشدات، وفي ضوء نتائج الدراسة وضع الباحثون عدد من التوصيات والمقترحات
Keywords: الإرشاد التربوي -- المرشدين التربويين -- الصحة لنفسية -- المدارس الثانوية -- محافظة ديالي -- العراق